Exploring novel systemic biomarker approaches in grass‐pollen sublingual immunotherapy using omics. Issue 4 (22nd September 2020) - Barker‐Tejeda, Tomas Clive; Bazire, Raphaelle; Obeso, David; Mera‐Berriatua, Leticia; Rosace, Domenico; Vazquez‐Cortes, Sonia; Ramos, Tania; Rico, Maria del Pilar; Chivato, Tomás; Barbas, Coral; Villaseñor, Alma; Escribese, Maria M.; et al.
Abstract: Background: Sublingual allergen‐specific immunotherapy (SLIT) intervention improves the control of grass pollen allergy by maintaining allergen tolerance after cessation. Despite its widespread use, little is known about systemic effects and kinetics associated to SLIT, as well as the influence of the patient sensitization phenotype (Mono‐ or Poly‐sensitized). In this quest, omics sciences could help to gain new insights to understand SLIT effects. Methods: 47 grass‐pollen‐allergic patients were enrolled in a double‐blind, placebo‐controlled, multicenter trial using GRAZAX® during 2 years. Immunological assays (sIgE, sIgG4, and ISAC) were carried out to 31 patients who finished the trial. Additionally, serum and PBMCs samples were analyzed by metabolomics and transcriptomics, respectively. Based on their sensitization level, 22 patients were allocated in Mono‐ or Poly‐sensitized groups, excluding patients allergic to epithelia. Individuals were compared based on their treatment (Active/Placebo) and sensitization level (Mono/Poly). Results: Kinetics of serological changes agreed with those previously described. At two years of SLIT, there are scarce systemic changes that could be associated to improvement in systemic inflammation. Poly‐sensitized patients presented a higher inflammation at inclusion, while Mono‐sensitized patients presented a reduced activity of mast cells and phagocytes as an effect of the treatment. Conclusions: The most relevant systemic change detected after two years of SLIT was the desensitization of effector cells, which was only detected in Mono‐sensitized patients. This change may be related to the clinical improvement, as previously reported, and, together with the other results, may explain why clinical effect is lost if SLIT is discontinued at this point. Abstract : In this study, omics strategies are used to identify mechanisms underlying SLIT in a prospective, double‐blind, placebo‐controlled study. The systemic effect induced by 2 years of SLIT is mediated by the downregulation of effector cells. Mono‐ and poly‐sensitized patients present differential systemic inflammatory signatures before starting SLIT. Abbreviations: PBMCs, peripheral blood mononuclear cells; SLIT, sublingual allergen‐specific immunotherapy.